Zum österreichischen Deutsch - SCHLAFFKE, Robert (Wydawnictwo Naukowe UAM, 1997)
The author presents the most fundamental differences between the Austrian (or rather southern German) and the northern variety of this language. The description covers the phonetic, morphological and syntactic level. Lexis is excluded, as this would go beyond the framework of this short article.